Power Domination and Resistance in George Orwell's Shooting an Elephant and Louise Erdrich's Snares - Dhakal, Sedunath (Janabhawana Research Journal, 2025)
This article examines the relationship between power and resistance as depicted in George Orwell’s ‘Shooting an Elephant’ and Louise Erdrich’s ‘Snares’. Power is viewed as a complex social structure that enables domination and creates inequality between groups. In response, resistance emerges in different forms, either direct or indirect. Using theoretical insights from Michel Foucault, Lila Abu-Lughod, and James C. Scott, this article explores how marginalized individuals resist dominant forces through both public and hidden actions. In ‘Shooting an Elephant’, the Burmese people show subtle, indirect resistance to British colonial rule, with the killing of the elephant which symbolizes decline of imperial power reflecting a quiet but powerful form of protest. On the other hand, ‘Snares’ presents a more open and direct form of resistance, as Native American characters fight back against the exploitation and land-grabbing of immigrant settlers. By comparing these two texts, the article shows how resistance, though shaped by time, place, and social conditions, is a natural response to power. Both texts illustrate that even those with limited means can find ways—symbolic or direct—to challenge domination.